A System of Indicators for the Quality Assessment of Didactic Materials in Online Education - Marciniak, Renata; Cáliz Rivera, Cristina (International Review of Research in Open and Distributed Learning, 2021)
The quality of didactic materials is a source of concern for teachers, users, and educational institutions that offer online education. There is a lack of indicators to help assess the quality of three key types of didactic materials commonly used in online education: didactic units (i.e., materials that contain program contents), didactic guides (i.e., materials that provide information), and additional didactic materials (materials to deepen knowledge). The objective of this article is to present a system of indicators designed to assess the quality of these types of didactic materials and guide their creation process. The system was developed based on a critical analysis of existing models designed to assess the quality of digital didactic materials. The system was validated by 16 international experts in online education, and a trial application of the system assessed five didactic guides and didactic units used by online universities in three different countries. Results of the validation process were triangulated with relevant literature, allowing the authors to make decisions regarding changes to the system in terms of maintaining, reformulating, or removing indicators. The resulting system comprises 43 assessment indicators and serves as a guide for designers, teachers, and users in the creation and selection of didactic materials for use in online education and in the assessment of their quality.